Liquid crystal tunable claddings for polymer integrated optical waveguides - Otón, José Manuel; Caño-García, Manuel; Gordo, Fernando; Otón, Eva; Geday, Morten Andreas; Quintana, Xabier (Beilstein Journal of Nanotechnology, 2019)
Optical waveguides in photonic integrated circuits are traditionally passive elements merely carrying optical signals from one point to another. These elements could contribute to the integrated circuit functionality if they were modulated either by variations of the core optical properties, or by using tunable claddings. In this work, the use of liquid crystals as electro-optically active claddings for driving integrated waveguides has been explored. Tunable waveguides have been modeled and fabricated using polymers. Optical functions such as variable coupling and optical switching have been demonstrated.
Keywords: liquid crystal; organic waveguide; photonic integrated circuit; polymer waveguide; tunable cladding

PIC International | 2016 Event

Moore’s Law - Thackray, A.; Brock, D.; Jones, R. (Basic Books, 2015)

(untitled) - Miller, S. E. (Bell Syst. Tech. J., 1969)

(untitled) - Smit, M.; van der Tol, J.; Hill, M. (Laser Photonics Rev., 2012)

(untitled) - Rickman, A. (Nat. Photonics, 2014)

(untitled) - Jahani, S.; Kim, S.; Atkinson, J.; Wirth, J. C.; Kalhor, F.; Noman, A. A.; Newman, W. D.; Shekhar, P.; Han, K.; Van, V.; DeCorby, R. G.; Chrostowski, L.; et al. (Nat. Commun., 2018)

(untitled) - Leuthold, J.; Koos, C.; Freude, W. (Nat. Photonics, 2010)

(untitled) - Pérez, D.; Gasulla, I.; Crudgington, L.; Thomson, D. J.; Khokhar, A. Z.; Li, K.; Cao, W.; Mashanovich, G. Z.; Capmany, J. (Nat. Commun., 2017)

(untitled) - Xia, F.; Rooks, M.; Sekaric, L.; Vlasov, Y. (Opt. Express, 2007)

(untitled) - Komma, J.; Schwarz, C.; Hofmann, G.; Heinert, D.; Nawrodt, R. (Appl. Phys. Lett., 2012)

(untitled) - Chung, L.-W.; Lee, S.-L.; Lin, Y.-J. (Opt. Express, 2006)

(untitled) - Dąbrowski, R.; Kula, P.; Herman, J. (Crystals, 2013)

(untitled) - Caño-García, M.; Geday, M. A.; Gil-Valverde, M.; Quintana, X.; Otón, J. M. (Beilstein J. Nanotechnol., 2018)

Microresist Technology

Microresist Technology

(untitled) - Caño-García, M.; Elmogi, A.; Mattelin, M.-A.; Missinne, J.; Geday, M. A.; Otón, J. M.; Van Steenberge, G.; Quintana, X. (Opt. Express, 2018)

Photonics Research Laboratory, University of Maryland

(untitled) - Fallahkhair, A. B.; Li, K. S.; Murphy, T. E. (J. Lightwave Technol., 2008)